2021
DOI: 10.1039/d1ce00988e
|View full text |Cite
|
Sign up to set email alerts
|

Growth mechanism on graphene-regulated high-quality epitaxy of flexible AlN film

Abstract: We report a novel diffusion–adsorption regulation growth method in the epitaxy of AlN on graphene for the high-quality and transferable large-size AlN film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…A few studies on transferring AlN thin films to flexible adhesive substrates have been reported recently. [54][55][56] However, there exist three issues: 1) the AlN crystalline quality, e.g., grain size, crystal orientation, in the above-mentioned studies is rather low due to the growing methods, which are limited by the growth approaches; 2) the adhesive handling materials during the transfer can leave residues on the AlN film; 3) only adhesive flexible substrates have been demonstrated as the final host substrate, which eliminate the potential of applications such as AlN-based vertical devices. [4] Hence, it is desirable to overcome the above issues and achieve a high-quality transferrable singlecrystalline AlN NM that can be transferred to a broader range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies on transferring AlN thin films to flexible adhesive substrates have been reported recently. [54][55][56] However, there exist three issues: 1) the AlN crystalline quality, e.g., grain size, crystal orientation, in the above-mentioned studies is rather low due to the growing methods, which are limited by the growth approaches; 2) the adhesive handling materials during the transfer can leave residues on the AlN film; 3) only adhesive flexible substrates have been demonstrated as the final host substrate, which eliminate the potential of applications such as AlN-based vertical devices. [4] Hence, it is desirable to overcome the above issues and achieve a high-quality transferrable singlecrystalline AlN NM that can be transferred to a broader range of substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some two-dimensional (2D) materials have been applied in the growth of GaN and other materials. That is, van der Waal epitaxy (vdWE) based on 2D materials. Among the common 2D materials, graphene is a better choice due to its excellent stability, in-plane hexagonal lattice arrangement, and the more mature preparation technology.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they prepared a large‐area and flexible AlN film with minimal damage. [ 81 ] The MLG layers (0.5 nm) were first grown on a Cu foil via CVD and transferred to the two‐inch sapphire substrate. As the growth time of AlN increased, the growth processes of the AlN film exhibited four stages: I) diffusion‐dominated stage; II) combined‐effect stage; III) adsorption‐dominated stage; IV) decomposition‐dominated stage.…”
Section: Iii‐nitride Epitaxy Based On 2d Materialsmentioning
confidence: 99%
“…Raman mapping of d) AlN (657 cm −1), e) graphene (2690 cm −1 ), and f) sapphire (417 cm −1 ) on the sample after peeling. Reproduced with permission [81]. Copyright 2021, Royal Society of Chemistry.…”
mentioning
confidence: 99%